2022
DOI: 10.3390/ijerph19127507
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, Physical Activity and Dietary Habits of Medical Students of Wroclaw Medical University during the COVID-19 Pandemic

Abstract: The new disease COVID-19, induced by SARS-CoV-2, causes acute respiratory infection. Many countries, including Poland, began to set a variety of different restrictions to reduce the spread of the virus. Most students had problems with online lessons. The study was conducted among second year medicine students of the Medical University of Wroclaw, and after the entire process of verification 200 respondents were accepted. The research consisted of completing the same anonymous online questionnaires twice in Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
8
1
1
Order By: Relevance
“…On the other hand, a study in Brazil reports that more than 20% of respondents have no or less alcohol consumption, with an increase of only 7.5% ( 67 ). Our previous study on medical students in Wrocław is similar, when we obtained an average decrease in alcohol consumption by 20% ( 60 ). In contrast, the results from the current nursing study show an initial decline and lowest risk of alcohol dependence in T1 compared to T0.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the other hand, a study in Brazil reports that more than 20% of respondents have no or less alcohol consumption, with an increase of only 7.5% ( 67 ). Our previous study on medical students in Wrocław is similar, when we obtained an average decrease in alcohol consumption by 20% ( 60 ). In contrast, the results from the current nursing study show an initial decline and lowest risk of alcohol dependence in T1 compared to T0.…”
Section: Discussionsupporting
confidence: 67%
“…Our research carried out on nursing students in Wrocław, shows a similar trend as research conducted at other universities. Although in our own study, conducted on medical students, we did not obtain statistically significant results due to the low level of activity already before the COVID-19 pandemic, we now recorded significant changes caused by it ( 60 ). Therefore, the working hypothesis about the negative pandemic impact on the physical activity of students is confirmed.…”
Section: Discussioncontrasting
confidence: 58%
“…In a 2019 study involving medical-related students in Poland, comparable findings were observed, indicating a marginally lower level of nutritional knowledge, with an insufficient level of 18.7%, sufficient at 68.2%, and good at 13.1% [ 85 ]. A subsequent Polish study conducted in October 2020 amid the COVID-19 pandemic reported even more unfavorable outcomes, revealing an insufficient nutritional knowledge level of 21%, sufficient at 61.5%, and good at 17.5% [ 86 ]. Furthermore, an investigation focusing on first-year physical education students in Warsaw unveiled notably poorer levels of nutritional knowledge, with an insufficient level of 37%, satisfactory at 59.3%, and good at 3.7% [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cases where the study was longitudinal and reported prevalence rates at several time-points [40][41][42][43][44][45][46][47][48][49][50][51][52][53], the most recent prevalence data were used. When the article provided prevalence rates of various countries (i.e.…”
Section: Study Selection and Data Extractionmentioning
confidence: 99%